Social Inclusion-Based Library Transformation Fostered by The Library and Archives Service of West Java - Silvina, Erliani; Prijana, Prijana; Rohman, Asep Saeful (Universitas Pendidikan Indonesia, 2023)
This research describes how the Library and Archives Service of West Java Province implements the Social Inclusion-Based Library Transformation program starting with preparations, strategies, policies, etc. By using qualitative methods with a case study approach. Researchers obtained primary data in this study through field observations, interviews, and notes on situations, conditions, and processes of the Social Inclusion-Based Library Transformation program. Researchers took secondary data in this study through scientific books, articles, journals, and previous studies. The results showed that the West Java Dispusipda had procedures in place when implementing the Social Inclusion-Based Library Transformation program through preparation, librarian training, program implementation, post-program advocacy, and evaluation. This institution also implements the Social Inclusion-Based Library Transformation program with a synergistic team of several government agencies and private institutions with the authority and capacity to succeed in this program. Constraints and obstacles experienced in running this program are 1. Lack of public understanding of the Social Inclusion-Based Library Transformation program; 2. The village head who does not take sides in the development of village information sources; 3. The community is still oriented towards government assistance.